Impacts of climate extremes on vegetation health in the tropical savannas of Africa - Jeanine Umuhoza; Guli Jiapaer; Yu Tao; Jie Bai; Egide Hakorimana; Liancheng Zhang; Hongwu Liang; Kaixiong Lin; Tongwei Ju (Global Ecology and Conservation, 2025)
The tropical savanna of Africa, which covers 65 % of the continent, supports livelihood, livestock, crops and wildlife, playing an important role in socio-economic development in Africa. However, these ecosystems experience high temperatures and distinct wet and dry seasons, making them highly vulnerable to climate change, with shifts in temperature, precipitation, and drought posing significant threats to vegetation. Increasing droughts and altered rainfall patterns disrupt the balance of these ecosystems. This research employs linear regression analysis and boosted regression trees (BRT) to assess the influences of climatic factors, including precipitation, temperature, Vapor Pressure Deficit (VPD), Soil Moisture (SM) and drought, on vegetation health in the African tropical savanna from 2000 to 2020. The key results showed that: Based on the spatial distribution of annual solar-induced chlorophyll fluorescence (SIF) dynamics, 26.55 % of tropical savanna areas showed significant improvement, mainly in savanna and forest-savanna mosaic. In contrast, 5.56 % of areas experienced significant degradation, primarily in thickets and woodlands. Stable or non-vegetated areas, accounting for 13.76 %, were most common in grasslands and bushveld. The Boosted Regression Trees (BRT) analysis revealed that VPD and temperature were key drivers of tropical savanna dynamics, contributing 26 % and 21 %, respectively. Thickets and bushlands were particularly vulnerable to water stress and drought, with VPD and temperature playing significant roles in these conditions. This research provides valuable insights for formulating strategies to promote savanna restoration and efficient management by examining the effects of climatic conditions on vegetation health.